Metformin Increases Sensitivity of Melanoma Cells to Cisplatin by Blocking Exosomal-Mediated miR-34a Secretion. (29th November 2021) - Ge, Lan; Wu, Yaguang; Wan, Ming; You, Yi; Zhai, Zhifang; Song, Zhiqiang
Abstract : Melanoma, also known as malignant melanoma, is a type of cancer derived from the pigment-containing cells known as melanocytes. Cisplatin (CDDP) is widely used in the treatment of different types of tumors with high response rates, but it generally has low efficiency in melanoma. This study aimed to investigate whether metformin could sensitize the melanoma cell line A375 to cisplatin. Our results for the first time indicated that CDDP increased the miR-34a secretion by exosomes in melanoma A375 cells, which was, at least partially, related to the cisplatin resistance of melanoma cells. Moreover, metformin significantly sensitized A375 cells to cisplatin. Mechanistically, metformin significantly blocked the exosome-mediated miR-34a secretion induced by cisplatin. Our study not only reveals a novel mechanism that exosomal secretion of miR-34a is involved in the cisplatin resistance of melanoma cells but also provides a promising therapeutic strategy by synergistic addition of metformin.